2023
DOI: 10.3310/nihropenres.13329.1
|View full text |Cite
|
Sign up to set email alerts
|

What are women’s experiences of seeking to plan a vaginal breech birth? A systematic review and qualitative meta-synthesis

Abstract: Background: Guidelines for breech management at term emphasise choice and informed decision-making. Despite this, the choice of vaginal breech birth (VBB), is not always available or accessible. We aimed to describe the experiences of women seeking a VBB as reported in primary research and to offer strategies for improving this experience that are grounded in evidence. Methods: We conducted a systematic review and qualitative meta-synthesis of the results, using grounded theory analysis methods (PROSPERO regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(91 reference statements)
0
0
0
Order By: Relevance
“…This was consistent with the demand observed within the OptiBreech care pathway, yet no women planned a VBB when randomised to standard care. Multiple systematic reviews have suggested women encounter barriers to accessing support for a VBB within standard care, and that this option is only acceptable if the birth is likely to be attended by supportive and appropriately trained professionals [10,11] This is also consistent with qualitative work involving women receiving OptiBreech care [1] and feedback from our PPIE group. In the qualitative study, women reported numerous examples of coercive counselling to dissuade them from attempting a VBB [1].…”
Section: Plos Onesupporting
confidence: 62%
See 4 more Smart Citations
“…This was consistent with the demand observed within the OptiBreech care pathway, yet no women planned a VBB when randomised to standard care. Multiple systematic reviews have suggested women encounter barriers to accessing support for a VBB within standard care, and that this option is only acceptable if the birth is likely to be attended by supportive and appropriately trained professionals [10,11] This is also consistent with qualitative work involving women receiving OptiBreech care [1] and feedback from our PPIE group. In the qualitative study, women reported numerous examples of coercive counselling to dissuade them from attempting a VBB [1].…”
Section: Plos Onesupporting
confidence: 62%
“…Two and one member of the research team were service users with lived experience of planning a VBB. Additional service users with lived experience of planning a VBB participated as members of the research team during qualitative work to refine the OptiBreech care pathway intervention [1,11] and consensus work to identify and prioritise outcome measures [16,17]. Service users influenced the design of the trial in multiple ways.…”
Section: Ppiementioning
confidence: 99%
See 3 more Smart Citations